Postorthodontic Relapse Prevention by Administration of Grape Seed (Vitis vinifera) Extract Containing Cyanidine in Rats - Alhasyimi, Ananto Ali; Rosyida, Niswati Fathmah; Rihadini, Mufliha Santi (European Journal of Dentistry, 2019)
Objective The aim of this study was to analyze the effect of grape seed extract containing cyanidin on osteoclastogenesis (by means of receptor activator of nuclear factor-κ B ligand [RANKL] and osteoprotegerin [OPG] levels) and the number of osteoclasts during orthodontic relapse in Wistar rats.Materials and Methods This study is an in vivo quasi experimental research. A total of 32 male Wistar rats were used in the study, which were randomly split equally into two groups, grape seed (GS) and control group (CG). All rats were given an orthodontic force of 35 cN using a stainless steel 3-spin coil spring that was activated for 7 days and then conditioned to be passive. During this phase, the GS group was administered grape seed extract containing cyanidin once per day. Orthodontic appliances were removed from both groups afterward, and then the alveolar bone tissue was isolated consecutively according to observation days (days 1, 3, 7, and 14), while OPG and RANKL levels were analyzed in their gingival crevicular fluid using a specific enzyme-linked immunosorbent assay (ELISA). Tissues were then stained with hematoxylin–eosin (H&E) and observed under a light microscope to count the number of osteoclast cells. Data were analyzed statistically using an independent t-test (p < 0.05).Results The number of osteoclasts in the GS group was significantly lower than that in the CG group on all experiment days (p = 0.021; p = 0.001; p = 0.024; p = 0.001; p < 0.05). ELISA results showed that the RANKL level of the GS group was significantly lower on days 3 and 7 (p = 0.025; p = 0.039; p < 0.05), while the OPG level was significantly higher on days 1 and 3 in the GS group than in the CG group (p = 0.039; p = 0.021; p < 0.05).Conclusion Grape seed extract can prevent postorthodontic relapse movement by inhibiting osteoclastogenesis and reducing the number of osteoclasts in Wistar rats.
Keywords: orthodontic relapse; grape seed extract; cyanidin; osteoclast; osteoprotegerin